PERAN TRANSFORMATIF GURU DALAM REPRODUKSI PEMAHAMAN ISLAM DAMAI (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2012)
This work tries to explains contemporary phenomenon which opposes moderatism regime that is great capital in the building of Indonesia nation prosperity. That phenomenon is the glowing of strictness action which effort to abolish the other group which is difference among society community. The action is used by certain society groups. This writing shows the glowing phenomenon of fundamentalism-exclusivism specters that always ramble. The author sees significance of teacher’s playing role to reproduce the peace religiousness comprehension (Islam) in one hand, and reduce furious religiousness comprehension (Islam) in other hand. The purpose of the effort is to expel the fundamentalism-exclusivism specters.